Multiple‐micronutrient supplementation for women during pregnancy - Haider, Batool A (Cochrane Database Syst Rev, 2017)
BACKGROUND: Multiple‐micronutrient (MMN) deficiencies often coexist among women of reproductive age in low‐ to middle‐income countries. They are exacerbated in pregnancy due to the increased demands, leading to potentially adverse effects on the mother and developing fetus. Though supplementation with MMNs has been recommended earlier because of the evidence of impact on pregnancy outcomes, a consensus is yet to be reached regarding the replacement of iron and folic acid supplementation with MMNs. Since the last update of this Cochrane review, evidence from a few large trials has recently been made available, the inclusion of which is critical to inform policy. OBJECTIVES: To evaluate the benefits of oral multiple‐micronutrient supplementation during pregnancy on maternal, fetal and infant health outcomes. SEARCH METHODS: We searched the Cochrane Pregnancy and Childbirth Group's Trials Register (11 March 2015) and reference lists of retrieved articles and key reviews. We also contacted experts in the field for additional and ongoing trials. SELECTION CRITERIA: All prospective randomised controlled trials evaluating MMN supplementation with iron and folic acid during pregnancy and its effects on the pregnancy outcome were eligible, irrespective of language or the publication status of the trials. We included cluster‐randomised trials, but quasi‐randomised trials were excluded. DATA COLLECTION AND ANALYSIS: Two review authors independently assessed trials for inclusion and risk of bias, extracted data and checked them for accuracy. The quality of the evidence was assessed using the GRADE approach. MAIN RESULTS: Nineteen trials (involving 138,538 women) were identified as eligible for inclusion in this review but only 17 trials (involving 137,791 women) contributed data to the review. Fifteen of these 17 trials were carried out in low and middle‐income countries and compared MMN supplements with iron and folic acid versus iron with or without folic acid. Two trials carried out in the UK compared MMN with a placebo. MMN with iron and folic acid versus iron, with or without folic acid (15 trials): MMN resulted in a significant decrease in the number of newborn infants identified as low birthweight (LBW) (average risk ratio (RR) 0.88, 95% confidence interval (CI) 0.85 to 0.91; high‐quality evidence) or small‐for‐gestational age (SGA) (average RR 0.92, 95% CI 0.86 to 0.98; moderate‐quality evidence). No significant differences were shown for other maternal and pregnancy outcomes: preterm births (average RR 0.96, 95% CI 0.90 to 1.03; high‐quality evidence), stillbirth (average RR 0.97, 95% CI 0.87, 1.09; high‐quality evidence), maternal anaemia in the third trimester (average RR 1.03, 95% CI 0.85 to 1.24), miscarriage (average RR 0.91, 95% CI 0.80 to 1.03), maternal mortality (average RR 0.97, 95% CI 0.63 to 1.48), perinatal mortality (average RR 1.01, 95% CI 0.91 to 1.13; high‐quality evidence), neonatal mortality (average RR 1.06, 95% CI 0.92 to 1.22; high‐quality evidence), or risk of delivery via a caesarean section (average RR 1.04; 95% CI 0.74 to 1.46). A number of prespecified, clinically important outcomes could not be assessed due to insufficient or non‐available data. Single trials reported results for: very preterm birth < 34 weeks, macrosomia, side‐effects of supplements, nutritional status of children, and congenital anomalies including neural tube defects and neurodevelopmental outcome: Bayley Scales of Infant Development (BSID) scores. None of these trials reported pre‐eclampsia, placental abruption, premature rupture of membranes, cost of supplementation, and maternal well‐being or satisfaction. When assessed according to GRADE criteria, the quality of evidence for the review's primary outcomes overall was good. Pooled results for primary outcomes were based on multiple trials with large sample sizes and precise estimates. The following outcomes were graded to be as of high quality: preterm birth, LBW, perinatal mortality, stillbirth and neonatal mortality. The outcome of SGA was graded to be of moderate quality, with evidence downgraded by one for funnel plot asymmetry and potential publication bias. We carried out sensitivity analysis excluding trials with high levels of sample attrition (> 20%); results were consistent with the main analysis except for the findings for SGA (average RR 0.91, 95% CI 0.84 to 1.00). We explored heterogeneity through subgroup analyses by maternal height and body mass index (BMI), timing of supplementation and dose of iron. Subgroup differences were observed for maternal BMI for the outcome preterm birth, with significant findings among women with low BMI. Subgroup differences were also observed for maternal BMI and maternal height for the outcome SGA, indicating a significant impact among women with higher maternal BMI and height. The overall analysis of perinatal mortality, although showed a non‐significant effect of MMN supplements versus iron with or without folic acid, was found to have substantial statistical heterogeneity. Subgroup differences were observed for timing of supplementation for this outcome, indicating a significantly higher impact with late initiation of supplementation. The findings between subgroups for other primary outcomes were inconclusive. MMN versus placebo (two trials): A single trial in the UK found no clear differences between groups for preterm birth, SGA, LBW or maternal anaemia in the third trimester. A second trial reported the number of women with pre‐eclampsia; there was no evidence of a difference between groups. Other outcomes were not reported. AUTHORS' CONCLUSIONS: Our findings support the effect of MMN supplements with iron and folic acid in improving some birth outcomes. Overall, pregnant women who received MMN supplementation had fewer low birthweight babies and small‐for‐gestational‐age babies. The findings, consistently observed in several systematic evaluations of evidence, provide a basis to guide the replacement of iron and folic acid with MMN supplements containing iron and folic acid for pregnant women in low and middle‐income countries where MMN deficiencies are common among women of reproductive age. Efforts could focus on the integration of this intervention in maternal nutrition and antenatal care programs in low and middle‐income countries.